Physicochemical and Vibration Analysis of Christmas Tree Four-Way Flange Failure under Fracturing Process - Zhaoming Zhou; Dawen Gong; Kelong Yang; Zhong Zeng; Zhou Xiao (Shock and Vibration)
When a wellhead gas production tree in a certain oilfield block fracturing completed 12 layers and 22 layers and then the bottom-up discharge operation was performed, the Wellhead four-way suddenly suffered erosion failure. This is the seventh failure of this operation. In order to obtain the cause of failure, the chemical analysis, hardness testing, tensile property testing, and finite element structural dynamic analysis are used to analyze the failure of the cross connection. The results of physical and chemical analysis show that the chemical composition, hardness, and tensile properties of the failed parts meet the requirements of the standard, not the problem of the material of the work piece. Due to the high-frequency vibration generated by the three-phase fluid in the pipeline during the discharge process, different types of vibration and deformation of the four-way valve and the valve body occur. The dimensions of the on-site structural parts were measured, and the bolt sizes were found to be different. A finite element model was established based on the measured data for dynamic analysis. Through physical and chemical tests and theoretical calculations, it is found that the cause of failure is the unbalanced load and resonance of the bolt, and the nut undercuts under high-frequency vibration, which causes leakage at the flange connection and eventually causes erosion failure. It is recommended to regularly use an electronic torque wrench to test the pretightening force of each bolt to prevent vibration and failure due to inconsistent pretightening force of the bolts.